2019
DOI: 10.1016/j.sjbs.2016.12.023
|View full text |Cite
|
Sign up to set email alerts
|

An estimation of the effects of synthetic auxin and cytokinin and the time of their application on some morphological and physiological characteristics of Medicago x varia T. Martyn

Abstract: The aim of the experiment was to determine the effects of synthetic auxin and cytokinin and the time of their application on some morphological and physiological characteristics of Medicago x varia T. Martyn grown under controlled conditions. The experiment was to check whether an application of exogenous hormones during vegetative and generative stages of the plant had an effect on above-ground mass development, on nitrate reductase activity and on plastid pigments content. Experiment factor was synthetic aux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
(39 reference statements)
0
14
0
1
Order By: Relevance
“…The effect of PGRs and PGPRs treatment was more pronounced in the sensitive genotype compared to the tolerant genotype. Previous studies demonstrated that the drought-induced reduction in chlorophyll content and chlorophyll fluorescence led to a decrease in photosynthesis and overall plant growth [55, 56]. The combined treatment significantly enhanced the chlorophyll fluorescence and chlorophyll content values in the PGRs/PGPRs treated plants in both genotypes.…”
Section: Discussionmentioning
confidence: 73%
“…The effect of PGRs and PGPRs treatment was more pronounced in the sensitive genotype compared to the tolerant genotype. Previous studies demonstrated that the drought-induced reduction in chlorophyll content and chlorophyll fluorescence led to a decrease in photosynthesis and overall plant growth [55, 56]. The combined treatment significantly enhanced the chlorophyll fluorescence and chlorophyll content values in the PGRs/PGPRs treated plants in both genotypes.…”
Section: Discussionmentioning
confidence: 73%
“…All of the isolated endophytic fungi were found to promote the growth of O. sativa L. “Cempo Ireng” [ 70 ]. Concerning the effect of exogenously applied hormones on plant growth, spraying exogenous auxins and cytokinin such as IAA and 6-benzylaminopurine resulted in an asymmetrical response of the treated alfalfa plants during their vegetative growth, while their application as a mixture was most effective and increased the biomass of plant shoots; however, the clearest effect was for the rate of total chlorophyll to carotenoid content [ 71 ]. Some endophytic fungi isolated from maize and rice plants, such as Fusarium , Sarocladium , Aspergillus and Penicillium , have been confirmed to be determining factors in plant growth improvement [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…This same method (via leaves) stood out, when compared to the application via ovary, for all proportions, except for 0/100%. Sosnowski et al (2016) stated that the cytokinin applied during the vegetative stage induces the increase in the number of leaves, but diminishes their expansion. However, as seen in this paper, cytokinin in equal proportion with auxin, applied on the leaves, may promote a better relationship between the expansion and the number of leaves, with a direct action on the organ, when compared with the application via ovary.…”
Section: Resultsmentioning
confidence: 99%